2023
DOI: 10.1021/acsami.3c04301
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of MBenes Supercapacitors: Fluorine-Free Synthesized MoAl1–xB with Ultrahigh Conductivity and Open Space

Abstract: The present study describes the synthesis of multilayered MBenes MoAl1–x B with different degrees of Al deintercalation using a mild, fluorine-free approach of dilute alkali to remove Al from MoAlB. We propose an etching route and compare it to conventional fluoride etching products. Additionally, the study explores the possible application and energy storage mechanism of MBenes in supercapacitors, marking the first investigation of its kind. At room temperature, 1/24-MoAl1–x B with terminal groups −OH exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…2e, the Al 2p spectrum of MoAlB performed three fitted peaks centered at 71.9, 74.2 and 74.8 eV, corresponding to elemental Al, MoAlB and Al 2 O 3 respectively. 39,40 Furthermore, similar to MoAlB, the Mo 3d spectrum of MBene-620 was also fitted to three couples for MBene, Mo-metal and Mo 6+ , respectively, as illustrated in Fig. 2f.…”
Section: Resultsmentioning
confidence: 94%
“…2e, the Al 2p spectrum of MoAlB performed three fitted peaks centered at 71.9, 74.2 and 74.8 eV, corresponding to elemental Al, MoAlB and Al 2 O 3 respectively. 39,40 Furthermore, similar to MoAlB, the Mo 3d spectrum of MBene-620 was also fitted to three couples for MBene, Mo-metal and Mo 6+ , respectively, as illustrated in Fig. 2f.…”
Section: Resultsmentioning
confidence: 94%
“…Partially “Al” etched MoAlB nanosheets are reported to show good energy storage performance when used as the electrodes of supercapacitors (Table 1 ). [ 70 , 71 , 72 ] 2D MBenes applied as the pseudocapacitive filter electrochemical supercapacitor electrode material exhibited excellent AC filtering performance with a specific capacitance of 702 mFcm −2 under the AC condition of 120 Hz and a negative phase angle of 54.8°. [ 70 ] All‐solid‐state supercapacitors based on multilayered MBenes delivered significant capacitance, high energy density, and power density even at a 90° bending angle ( Figure 7 ).…”
Section: Applications Of Molybdenum Borides and Mbenesmentioning
confidence: 99%
“…[ 70 ] All‐solid‐state supercapacitors based on multilayered MBenes delivered significant capacitance, high energy density, and power density even at a 90° bending angle ( Figure 7 ). [ 71 ] Vinoth et al demonstrated the asymmetric supercapacitors based on MoB nanosheets and activated carbon as the electrodes with 1 M H 2 SO 4 and 1 M Na 2 SO 4 as the electrolytes. [ 72 ] The asymmetric device delivered a high energy density of 14 WhKg −1 at a power density of 16.8 kWKg −1 .…”
Section: Applications Of Molybdenum Borides and Mbenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to MXene, another 2D nanomaterial, MBene is obtained by selectively etching an A element from the precursor MAB phase (M is an early transition metal, A is a group A element, and B stands for boron element) . Theoretical calculations and experiments demonstrate the potential applications for MBene in catalysis, magnetic devices, energy storage , and conversion, biotechnology, solid lubrication, gas absorption, etc . Among various MBenes, MoB MBene has attracted great research attention in recent years due to the prospective catalytic activity provided by Mo sites.…”
mentioning
confidence: 99%